42=x-19

Simple and best practice solution for 42=x-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42=x-19 equation:



42=x-19
We move all terms to the left:
42-(x-19)=0
We get rid of parentheses
-x+19+42=0
We add all the numbers together, and all the variables
-1x+61=0
We move all terms containing x to the left, all other terms to the right
-x=-61
x=-61/-1
x=+61

See similar equations:

| 1/6x+3/2=-1/3 | | 6(x-6)+2=8(x+20-6 | | 3/11=x/x+9 | | (x-2)(x-5)=8 | | 1/4x=116 | | .2-1x+2.5=-3.6 | | a^2+(2a)^2=400 | | 13.5x=-7+94.5 | | 6x=19,5 | | 4y-3+y+33=7y+30-5y | | -8+3=-24+13x | | 4y-10+y+56=5y=50-2y | | 3v^+18v=0 | | -5(0.1x+0.2)-0.6=-0.1 | | 1.8x+3.6=6-4x+15 | | 2x=19/2 | | (6+u)(5u+9)=0 | | 883.39/1,257,521=x/1,007,369 | | 2(5x+20)=6(2x=4) | | 10x+8=9x+1 | | 8(8n+4)=4(-7n+8) | | 4m+3=23;6 | | y/3+4=5/3 | | 4/5x-3=2=9/10x | | r/6=8;48 | | (x+3)/4=(x/2)+(2/5) | | X³+2x-12=0 | | (x-5)/6=1-(x-5) | | (x+3)/5=(4x-3)/15 | | p/3-3/8p=5 | | F(x)=(x-1)(x+2) | | 3x+27=-x15 |

Equations solver categories